The health-economic burden of hip and knee periprosthetic joint infections in Europe: a comprehensive analysis following primary arthroplasty - Volker Alt; Dominik Szymski; Markus Rupp; Andreas Fontalis; Danguole Vaznaisiene; Leonard C. Marais; Christof Wagner; Nike Walter; on behalf the Country Delegates of the European Bone and Joint Infection Society* (Bone & Joint Open)
Aims: Periprosthetic joint infections (PJIs) pose significant challenges to patients and healthcare systems worldwide. The aim of this study was to estimate the health-economic burden of reimbursement payment in Europe for PJIs following primary hip and knee arthroplasty. Methods: The calculation was based on health-economic modelling using data on primary hip and knee arthroplasties for the year 2019 from the Statistical Office of the European Union (Eurostat) and published infection rates to estimate the total number of hip and knee PJIs in 30 European countries. Revision procedures were stratified into: 1) debridement, antibiotics, and implant retention (DAIR); 2) one-stage exchange; and 3) two-stage revision procedures. The cases were then multiplied by the respective healthcare system reimbursement payments. Payment data were acquired from a survey of 13 countries (Austria, Croatia, France, Germany, Italy, Lithuania, Netherlands, Norway, Portugal, Slovenia, Switzerland, Turkey, and the UK) and extrapolated for the remaining countries. Results: In 2019, a total of 2,048,778 primary total joint replacements were performed (total hip arthroplasty (THA) = 1,147,316 and total knee arthroplasty (TKA) = 901,462), with an estimated 20,416 cases of PJIs (11,131 hip and 9,285 knee) in Europe. This results in an estimated total reimbursement burden of €346,262,026 for European healthcare systems. The breakdown for hip PJI reimbursement was €197,230,953 (€9,751,962 for DAIR procedures, €45,135,894 for one-stage revisions, and €142,343,097 for two-stage revisions). For knee PJIs, the analysis yielded a total reimbursement of €149,031,073 (€9,335,075 for DAIR procedures, €48,058,479 for one-stage revisions, and €91,637,518 for two-stage revisions). Conclusion: This is the first study to evaluate the health-economic burden of PJIs in Europe, revealing a substantial impact on healthcare systems with an estimated case load of 20,414 cases and overall reimbursement of €346,262,026 for primary THAs and TKAs performed in 2019. Cite this article: Bone Jt Open 2025;6(3):298–311.